THE EFFECT OF PRESS MEDIA FROM CERAMIC AND METAL MATERIALS ON THE TENSILE STRENGTH OF RECYCLED POLYPROPYLENE FOR THE DEVELOPMENT OF COMPOSITE MATRIX MATERIALS - Haris Ardianto; Hery Setiawan; Sehono Sehono; Maruli Tua Pranata (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Composites generally consist of fiber (filler) and resin (matrix). Resin from recycled polypropylene (plastic) polymer was chosen because it has superior properties compared to other types. The manufacturing process with a hot air melting temperature (heat gun) of 300oC was chosen with two variations of press media, namely metal and ceramic, to compare the mechanical properties of tensile strength. Specimens were shaped according to the ASTM D638 standard. The results showed that the recycled polypropylene with ceramic press media had an average tensile stress of 15.05 MPa, which was higher than that of compressed metal media of 13.06 MPa.